THE EFFECT OF FOOT STRENGTH AND SPEED TRAINING ON THE RESULTS OF THE EXTRACURICULAR ATHLETICATHLETIC LEVEL OF MTs. HIDAYATUL MUBTADI`IN BANYUWANGI DISTRICT - Ach. Zayul Mustain (International Jurnal of Education Schoolars, 2021)
Athletics is the oldest sport owned by humans, because its basic movements have been reflected in human life for a long time, namely walking, running, jumping and throwing. Athletics is a sport that underlies another sport of Florence in Maulana (2016). Furthermore, according to Bakar (2019) athletics is an effective physical activity to optimize children's growth and development. One of the categories of athletics, especially in jump numbers, is multi-jump. The type of research used in this study is a quasi experiment. According to Suharsimi Arikunto (2010), states that experimental research is research that is intended to determine whether or not there is a consequence of "something" imposed on the subject under investigation or under study. In other words, experimental research tries to examine whether there is a causal relationship, the way is to compare the conditions before and after being treated. The results of theexercise squat jump can increase leg muscle strength so that it can increase the jump distance in multiple jumps. The results of the t-test data analysis show a 2-tailed sig value <p-value (0.05) so that it can be concluded that there is an effect of Squat jump training on the jump jump results of Mts Hidayatul mubtadiin extracurricular athletic students 2019/2020.